Análisis del sistema de gestión de talento humano para la empresa florícola Puliza Flowers, Cayambe, provincia de Pichincha - Vivanco Herrera, Dayana Lizeth (2023)
The main objective of this study is to develop a model proposal for the management system of the Human Resources Department for the floriculture company Puliza Flowers, with the purpose that the organization develop management through regulations and instruments that improve subsystems such as recruitment and income. of employees, performance evaluation, compensation and development of employees. This research used a qualitative approach, developed in two phases (1) data collection and management information developed, (2) construction of the management system proposal according to the objectives of the organization. The finding determined in this research allows us to conclude that the organization lacks a management system of the Human Resources Department and an area in charge of its implementation in the organization where there is no assignment of responsibilities, difficulties in hiring due to the absence of defined job profiles, which has a direct influence at the time of applying performance evaluations and improvement of results. That is why through the application of this proposal solutions are established to solve the problems encountered.